Adolescência e violência: um estudo da medida socioeducativa de prestação de serviço a comunidade no município do Natal - Silva, Luana Gleyce Souza da (2009)
This Project was built to reflect about juvenile violence and the socio-educational´s range of community services provision. It is known that the juvenile violence is a phenomenon inserted on the capitalism system, backed on neo liberal project. Though, it is essential a historical analysis, showing the economical, political, social and cultural mechanisms which determine the juvenile violence personality. On this way, it is seek understand the elements that leads on work world changes, on the State and public politics sphere, that deepens social dissimilarities. On this propose, it is known that there is a relation among the violence, while one of many manifestations of social question on society and the macroestructuals´determinant that lead the teenager to a social rick situation. This research focused on a inquiry quail-quantitative, using the theoric-metodological procedures of observation, interview and documental quest techniques. The universe had been defined by the intentional sample of 22 interviewed on total, during August and October 2008, covering adolescents and their relatives, technical and the coordinator, which subsidized the Socio educational program of community services provision from Natal analysis of limits and their range. The results of this investigation indicate the necessity of development, with the teenagers authors of infringement acts, a care system that is grounded on a professional formation, respect on human rights and citizenship conquest, regarding that children and teenagers are designed as people on development, that have theirs rights and integral protection, being the State, society and family responsibility assure the integral development of them